Primary transoral robotic surgery +/‐ adjuvant therapy for oropharyngeal squamous cell carcinoma—A large observational single‐centre series from the United Kingdom. (31st May 2021) - O'Hara, James; Warner, Laura; Fox, Hannah; Hamilton, David; Meikle, David; Counter, Paul; Robson, Andrew; Goranova, Rebecca; Iqbal, Shahid; Kelly, Charles; Robinson, Max; Paleri, Vinidh
Abstract: Objectives: To analyse the oncological outcomes following primary Transoral Robotic Surgery (TORS) for oropharyngeal squamous cell carcinoma (OPSCC). Design: Observational case series. Setting: Tertiary centre; first TORS practice to commence in the UK. Participants: All consecutive patients undergoing primary TORS with curative intent, with or without adjuvant treatment. Main outcome measures: Descriptive analysis of patient and tumour pathology variables. Survival outcomes: Overall, Disease‐Specific, Progression‐Free and Locoregional control. Results: The cohort comprised of 120 patients undergoing TORS with minimum 12‐month follow‐up data and the following characteristics: mean age 58 years, 91 males (76%), 78 tonsil (65%) and 34 base of tongue primaries (28%), 89% HPV‐related OPSCC. The surgical pathology revealed 14 (12%) with positive margins, 19 (16%) had close margins <2mm and 31% with extranodal extension. The treatment was as follows: 39 (33%) treated with TORS alone, 50 (42%) received adjuvant radiotherapy and 31 (26%) received adjuvant radiotherapy with chemotherapy. There were 15 recurrences. Estimated survival for all patients at 3 years (95% CI): overall 85% (78‐92), disease‐specific 90% (85‐96), progression‐free 86% (79‐92) and locoregional control 90% (84‐96). The equivalent survival figures for the HPV‐related cases alone were as follows: overall 88% (82‐94), disease‐specific 93% (87‐98), progression‐free 88% (81‐95) and locoregional control 92% (87‐98). Conclusions: Whilst TORS has become a common practice in the management of OPSCC in the UK, these are the first reported oncological outcomes. For selected patients, TORS with or without adjuvant therapy is an appropriate treatment modality.